Industrial training report: TE Synergy (M) Sdn. Bhd. / Nur A’dnin Azman - Azman, Nur A’dnin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about my experience as an intern at an information agency through my industrial training program in semester 5. My company of choice was TE Synergy (M) Sdn. Bhd. which is located at 5 – 2, Jalan Wangsa Delima 10, Wangsa Link, Wangsa Maju, 53300 Kuala Lumpur. This internship took place on the 22nd of July 2024 during my semester break. This industrial training program was implemented to give the students a chance to experience a working environment and to let them explore their skill set and how they can be applied to the tasks they are assigned to. Through this program, I was able to assess my abilities and limits when I was given a task to do as well as learn how to overcome the challenges I was faced with as minimal assistance from my superiors as possible. I also learned how to become more independent, confident and discovered more about myself and my capabilities from it.